Case report: Irinotecan-induced interstitial lung disease in an advanced colorectal cancer patient resurfacing decades after allogeneic bone marrow transplantation for aplastic anemia; a case report and narrative review of literature - Baba, Keisuke; Matsubara, Yasuo; Hirata, Yoshihiro; Ota, Yasunori; Takahashi, Satoshi; Boku, Narikazu (Frontiers in Oncology, 2023)
Two mechanisms of drug-induced interstitial lung disease (DILD) have been reported: 1) direct injury of lung epithelial cells and/or endothelial cells in lung capillaries by the drug and/or its metabolites and 2) hypersensitivity reactions. In both mechanisms, immune reactions such as cytokine and T cell activation are involved in DILD. While past and present lung diseases and accumulative lung damage due to smoking and radiation are risk factors for DILD, the association between the immune status of the host and DILD is not well known. Herein, we report a case of advanced colorectal cancer with a history of allogeneic bone marrow transplantation for aplastic anemia more than 30 years prior, in which DILD occurred early after irinotecan-containing chemotherapy. Bone marrow transplantation might be a potential risk factor for DILD.